2012
DOI: 10.1111/j.1365-2621.2012.03204.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of reaction kinetics of hydrolysis of tilapia (Oreochromis niloticus) protein for manipulating production of bioactive peptides with antioxidant activity, angiotensin‐I‐converting enzyme inhibitory activity and Ca‐binding properties

Abstract: Summary To manipulate enzymatic hydrolysis of tilapia (Oreochromis niloticus) muscle protein for production of bioactive peptides, its reaction kinetics was intensively studied. The study showed that the production of peptides with different bioactive properties including antioxidant activity, angiotensin‐I‐converting enzyme (ACE) inhibition and Ca‐binding property and their kinetics were affected by the degree of hydrolysis and substrate concentration. A comparative study on reaction kinetics found that the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
2
10
0
2
Order By: Relevance
“…As a result, ACE inhibitors from natural sources have gained increasing attention as a functional food. Many ACE inhibitory peptides have been isolated from enzymatically hydrolyzed fish proteins including sardine (Matsui et al, 1993), yellowfin (Jung et al, 2006), seaweed pipefish (Wijesekara, Qian, Ryu, Ngo, & Kim, 2011), grass carp (Chen, Wang, Zhong, Wu, & Xia, 2012), tilapia (Charoenphun, Youravong, & Cheirsilp, 2013;Raghavan & Kristinsson, 2009), and brownstripe red snapper (Khantaphant, Benjakul, & Kishimura, 2011). Tilapia (Oreochromis niloticus) is an important aquacultured freshwater fish, with the global production of approximately 4 million metric tonnes in 2011; and it is expected to exceed 4.5 million metric tonnes in 2015 (Fitzsimmons, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, ACE inhibitors from natural sources have gained increasing attention as a functional food. Many ACE inhibitory peptides have been isolated from enzymatically hydrolyzed fish proteins including sardine (Matsui et al, 1993), yellowfin (Jung et al, 2006), seaweed pipefish (Wijesekara, Qian, Ryu, Ngo, & Kim, 2011), grass carp (Chen, Wang, Zhong, Wu, & Xia, 2012), tilapia (Charoenphun, Youravong, & Cheirsilp, 2013;Raghavan & Kristinsson, 2009), and brownstripe red snapper (Khantaphant, Benjakul, & Kishimura, 2011). Tilapia (Oreochromis niloticus) is an important aquacultured freshwater fish, with the global production of approximately 4 million metric tonnes in 2011; and it is expected to exceed 4.5 million metric tonnes in 2015 (Fitzsimmons, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, several commercial proteinases such as Alcalase (Charoenphun et al, 2013;Chen et al, 2012;Intarasirisawat, Benjakul, Wu, & Visessanguan, 2013), pepsin (Sheih, Fang, & Wu, 2009;Wang et al, 2008), trypsin (Asoodeh et al, 2012;Lee, Jeon, & Byun, 2014), thermolysin (Ghassem, Arihara, Babji, Said, & Ibrahim, 2011), and Flavourzyme (Khantaphant et al, 2011) have been used to produce protein hydrolysates with ACE inhibitory peptides. However, the use of proteinases from novel sources in protein hydrolysate production has not been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this suggested that these low molecular mass peptides from the enzymatic hydrolysis of EWPs could have a higher ABTS radical scavenging efficacy than other molecular mass peptides, contributing for higher antioxidant activity of the hydrolysate prepared after ultrasound pretreatment. Earlier studies have shown that the majority of the antioxidative peptides derived from food sources have molecular weights ranging from 500 to 1,800 Da [20,48]. In future studies, the antioxidant properties of each fraction will be tested.…”
Section: Effect Of Ultrasound Pretreatment On Antioxidant Activity Ofmentioning
confidence: 97%
“…Nile tilapia ( O. niloticus ) is widely cultivated and consumed species among freshwater fishes reared in Thailand. There are some reports describing bioactive peptides from tilapia (Foh et al ., ; Charoenphun et al ., ). Recently, we found that ultrasonic pretreatment can enhance antioxidative activity of tilapia protein hydrolysate.…”
Section: Introductionmentioning
confidence: 97%